Vegetation and flora of the Kosi Bay Coastal Forest Reserve in Maputaland, northern KwaZulu-Natal, South Africa - Van Wyk, Abraham Erasmus (Braam) (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 1996.